1999
DOI: 10.1016/s0895-7061(98)00230-1
|View full text |Cite
|
Sign up to set email alerts
|

V2-receptor–mediated relaxation of human renal arteries in response to desmopressin

Abstract: The effects of deamino-8-D-arginine vasopressin (desmopressin), a V 2 receptor antidiuretic agonist, were studied in isolated rings from branches of renal arteries obtained from 22 patients undergoing nephrectomy. The rings were suspended in organ bath chambers for isometric recording of tension. In precontracted rings with norepinephrine (10 ؊6 to 3 ؋ 10 ؊6 mol/L), desmopressin (10 ؊11 to 3 ؋ 10 ؊7 mol/L) caused endothelium-dependent relaxation (81% ؎ 4% reversal of the initial contraction in arteries with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(22 reference statements)
3
20
0
Order By: Relevance
“…Furthermore, V 2 -related renal vasodilation has been reported with desmopressin and, after V 1 receptor antagonist pretreatment, with vasopressin directly infused in vivo into the canine renal artery (Naitoh et al 1993;Aki et al 1994). In rabbit afferent arterioles, desmopressin elicits relaxation mediated by V 2 receptor stimulation (Tamaki et al 1996), as was also reported recently for human renal arteries (Medina et al 1999). However, we were unable to find any renal vasorelaxation linked to V 2 receptor activation in the rat.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, V 2 -related renal vasodilation has been reported with desmopressin and, after V 1 receptor antagonist pretreatment, with vasopressin directly infused in vivo into the canine renal artery (Naitoh et al 1993;Aki et al 1994). In rabbit afferent arterioles, desmopressin elicits relaxation mediated by V 2 receptor stimulation (Tamaki et al 1996), as was also reported recently for human renal arteries (Medina et al 1999). However, we were unable to find any renal vasorelaxation linked to V 2 receptor activation in the rat.…”
Section: Discussionsupporting
confidence: 66%
“…These clinical observations strongly supported the existence of extrarenal V2Rs, and later studies positively confirmed V2R effects in the endothelium (55,75): the endothelial V2R, activated by desmopressin in high doses and by equivalent blood concentrations of endogenous AVP (56), releases vWF and factor VIII from Weibel-Palade bodies (Fig. 2).…”
supporting
confidence: 64%
“…Extrarenal V2Rs, primarily located in endothelial cells (Fig. 2), have been shown to increase the circulating levels of coagulation factor VIII, vWF, and tissue plasminogen activator (56,75).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 99%
“…However, a number of studies have now well documented the existence of extrarenal V2 receptors, probably located on the vascular endothelium (29). The stimulation of these receptors by V2 agonists results in a significant vasodilation (30,31) that probably accounts for the fall in BP observed in this study (20,22).…”
Section: Discussionmentioning
confidence: 49%